The Impact of Religious Moderation in School Uniform Policies: A Mixed-Methods Analysis on Student Well-Being in Indonesia - Ade Husna; Zahrotus Saidah; Sri Widyastri; Hilwah Hawaassa Asmawi (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
ABSTRACT This study examines how religious moderation is operationalized through school uniform policies and how these policies influence student well-being in Indonesian public senior high schools and vocational schools. Although previous research has explored religious moderation in madrasahs and the politics of hijab regulation, limited studies have integrated religious moderation policy, uniform regulation, and student well-being within a single analytical framework. This study addresses that gap by analysing how inclusive uniform rules shape students’ daily experiences, identity expression, and sense of belonging. A mixed-methods design was employed, combining survey data from 110 students across four schools in West Sumatra and Central Java with qualitative interviews and document analysis. Quantitative data were analysed descriptively, while qualitative responses were coded thematically. The findings show three key results. First, uniform regulations that neither mandate nor prohibit religious attire are widely perceived as supportive, with 99.1 percent of students reporting no disruption to their school activities. Second, 98.2 percent believe that current policies reflect multicultural values, indicating alignment with national religious moderation guidelines. Third, wearing the hijab has become a personal habit for most Muslim female students, suggesting that policy neutrality does not diminish religious identity. These findings demonstrate that inclusive uniform policies strengthen students’ psychological comfort, social cohesion, and cultural respect. The study concludes that schools should maintain flexible uniform regulations and integrate religious moderation principles to promote equitable and harmonious learning environments. ABSTRAK Studi ini membahas bagaimana moderasi beragama diimplementasikan melalui aturan seragam sekolah dan bagaimana aturan ini terkait dengan kesejahteraan siswa di sekolah menengah negeri di Indonesia. Dengan menggunakan analisis metode campuran, data diperoleh dari 110 siswa di tiga sekolah kejuruan dan sekolah menengah atas di Jawa Tengah dan Sumatera Barat. Wawancara, analisis dokumen, survei, dan tinjauan pustaka dilakukan untuk mengeksplorasi pengalaman dan persepsi siswa. Temuan menunjukkan bahwa moderasi beragama terungkap dalam peraturan seragam saat ini, yang tidak melarang atau mewajibkan siswa untuk mengenakan pakaian keagamaan seperti jilbab. Siswa sebagian besar menemukan kebijakan ini mendukung dan inklusif terhadap keberagaman, dengan 99,1% mengakui bahwa peraturan seragam tidak membebani kegiatan sehari-hari mereka dan 98,2% mengakui bahwa kebijakan saat ini mencerminkan nilai-nilai multikultural. Analisis ini menunjukkan bahwa peraturan seragam yang inklusif dapat melahirkan rasa memiliki, identitas, dan kenyamanan psikologis yang positif, memperkuat lingkungan pendidikan multikultural demi kesejahteraan siswa. Studi ini mengungkap kontribusi baru dengan memadukan regulasi yang seragam, kebijakan moderasi beragama, dan kesejahteraan ke dalam kerangka analitis, yang menawarkan rekomendasi yang berarti bagi para pendidik, pemimpin sekolah, dan pembuat kebijakan untuk menyediakan lingkungan belajar yang harmonis dan inklusif.